Ocular clinical manifestations in patients diagnosed with ophthalmic herpes zoster - Mamani Maquera, Diego José (2022)
Objective: To know the ocular clinical manifestations in patients diagnosed with herpes zoster ophthalmicus (HZO) at the Carlos Alberto Seguín Escobedo National Hospital of EsSalud - Arequipa, in 2021. Material and methods: Observational and descriptive study. The population included all patients diagnosed with HZO who underwent a thorough eye examination. The data was processed and analyzed using the statistical program SPSS v24 and presented through tables and descriptive graphs. Results: 16 patients were included in the study. The average age was 73 years. 8 cases had high blood pressure, 6 cases had type II diabetes mellitus, and 2 cases had some type of neoplasm.The mean time between the manifestation of the skin rash and the search for medical help was 6 days. The most described ocular symptom was pain (62.5 %). Hutchinson’s sign was present in 12 patients (75 %), and they reported ocular symptoms in 100 % of them. The maximum difference between both eyes’ intraocular pressure (IOP) was 3 mmHg. Slit lamp examination revealed conjunctival hyperemia in five cases (31.3 %) and epithelial keratitis in five cases (31.3 %). Conclusion: The most affected population is the older adult who presents a condition of immunosuppression. Most presented ocular symptoms and Hutchinson’s sign (+), and most sought medical care over 72 hours after the onset of the rash.